The Production of Liquid Fuel from Plastic Wastes by Using Waste Garbage Power Plant: Study on the Effect of Electric Load and Fuel/Gasoline to Solar Ratio - Roni, Kiagus Ahmad; Mufrodi, Zahrul; Mustakim, Imam (Jurnal Bahan Alam Terbarukan, 2020)
The type of plastic waste that is often a problem in many cities in Indonesia is Polyethylene Terephthalate (PET), his is due to the plastic waste plastic waste bags has no longer economic value. One of the goals of plastic waste processing is usng it as a raw material for the Waste Garbage Power Plant (PLTSa). The most profitable in handling plastic waste by converting plastic waste into fuel oil as an alternative energy source because plastic is basically derived from petroleum. Plastic also has a fairly high heating value equivalent to gasoline and diesel fuel. Some studies related to plastic processing have not been integrated from the production process to downstream products in the form of electric products to get the overall level of plant efficiency. Therefore a research of plastic waste power plants needs to be done at the prototype level to determine the performance of the fuel and the level of efficiency of the resulting assemblers. The Pyrolysis Reactor Prototype Unit can be used to convert plastic bottle waste into liquid fuel with a yield of 56.26% carried out at a process temperature of 170 oC and the resulting heating value reaches 19644 Btu/lb close to the heating value of Pertamina Gasoline. The generator system performance test for the liquid fuel mixture (BBC) with Gasoline and Diesel has an optimal mixture ratio in the BBC - Bensi / Solar mixture 3: 2 with an optimal load of 800 Watt. In the generator system performance test for liquid fuel mixture (BBC) with Gasoline/Diesel is more optimal for comparison of BBC fuel with Gasoline, because for the BBC mixture with Gasoline in all generator system comparison values occur ignition. Whereas BBC with Solar does not ignite at a ratio of 0: 5, 1: 4 and 2: 3.